Synthesis, Crystal Structures, Electronic Spectra, and Magnetic Properties of Thiolato-Bridged Trinuclear Cobalt(II) Complexes with N, N, S-Tridentate Thiolate Ligands - Mikuriya, Masahiro; Fujita, Atsushi; Kotera, Takanori; Yoshioka, Daisuke; Sakiyama, Hiroshi; Handa, Makoto; Tsuboi, Motohiro (Universitas PGRI Semarang, 2021)
New trinuclear CoII complexes, [Co(apaet)22Co]X2 (apaet– = 2-[(3-aminopropyl)amino]ethanethiolato; X = SCN (1), ClO4 (2), NO3 (3), Cl (4), Br (5), I (6)) and [Co(apampt)22Co]X2 (apampt– = 1-[(3-aminopropyl)amino]-2-methylpropane-2-thiolato; X = NO3(7), ClO4 (8), Cl (9), Br (10), I (11)), and mononuclear CoIII complexes, [Co(apaet)2]X (X = ClO4 (12), NO3 (13)), were synthesized. Single-crystal X-ray crystallography of 1 and 7 confirmed that the trinuclear complexes have a linear arrangement of octahedral CoIIS2N4-tetrahedral CoIIS4-octahedral CoIIS2N4 chromophores where two thiolate ligands are coordinated to each terminal Co atom in a mer coordination mode and the two thiolato S atoms are further bound to the central Co atom, which is consistent with the electronic spectra and antiferromagnetic properties